A combined experimental and computational study of environmental stress cracking of amorphous polymers. (28th October 2019) - Koch, Simon; Meunier, Marc; Hopmann, Christian; Alperstein, David
Abstract : Environmental stress cracking (ESC) refers to a phenomenon causing the failure of polymeric materials such as thermoplastics. Although the precise mechanism is not fully understood, a few key incidents are known to be involved in the full failure process. Adsorbed fluid molecules on the polymer surface and their migration into the bulk material cause craze initiation and growth as well as eventually parts breakdown. The diffusion of the media inside the polymer, causing plasticization, is accepted to be one of the key incidents involved. Such materials degradation is a self‐sustained aging mechanism: local defects creating more free volume for fluid molecules to migrate into, causing more degradation until critical failure. Molecular modelling (MM) simulation techniques have been used in the present study for the first time in the ESC research to scrutinize the applicability of these techniques to the description of molecular events responsible for the various degradation steps. Molecular cross section, polymer‐fluid compatibility (as measured by the fluid solvation free energy), adsorption energies, etc, are possible descriptors to build up a quantitative structure‐activity relationship (QSAR) model to allow the prediction of the ESC risk presented by a fluid for a given polymer. Three amorphous polymers, namely, polystyrene (PS), polymethylmethacrylate (PMMA), and polycarbonate (PC), and various fluids (such as water and ethanol) have been modelled, using the above‐mentioned MM techniques.